A guidebook for volleyball-related health problems using Manga and educational activities for injury prevention: Volleyball 911. Issue 6 (10th April 2011) - Hayashi, M; Hamu, Y; Hashimoto, Y
Abstract : Background: Many Volleyball related health problems occur when players are junior and high school students, but there is a lack of knowledge of sports health issues among players and instructors. Objective: To educate players and instructors and therefore prevent health problems, by creating a guidebook. Setting: Medical checkups for volleyball players at all levels often reveal sports related issues including lower back pain, knee pain such as jumper's knee, shoulder pain caused by volleyball spikes, ankle joint sprain, digital deformities and anemia. When the history is examined it is often found that many of these problems began at junior or high school level. Result: 10 years ago, a guidebook for prevention of Volleyball-related injuries and health problems was prepared using easy-to-understand 'Manga' (comic-book illustrations) for both junior players and instructors. Approximately 10 000 copies of the guidebook were distributed for free. Currently, the guidebook is available on the website of the Japan Volleyball Association and educational activities for volleyball related health issues are being conducted. Conclusions: An English version of the guidebook was prepared for this FIVB Volleyball Medicine Congress. It is our wish that the guidebook be translated into many languages in order to protect valuable junior volleyball players around the world from sports-related injuries. With the help of the participants in the Congress, we ask that the guidebook be translated into their own languages. The goal is to promote educational activities through the website of the FIVB.